STUDI KASUS PERLAKUAN AKUNTANSI ASET BIOLOGIS BERDASARKAN IPSAS 27 AGRICULTURE PADA DINAS PERTANIAN X - Dina Natasari; Rizky Wulandari (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2019)
Agriculture activities are the elective matters that must be carried out by the local government to serve the interests of the community. The implication of these are the recognition of assets in the form of living animals and plants in government financial reports. This study analyzed the accounting treatment of biological assets based on International Public Sector Accounting Standard (IPSAS) 27 Agriculture on the agricultural service of a regional government. There are significant differences between the provisions of the applicable biological asset assessment in Pernyataan Standard Akuntansi Pemerintahan (PSAP) 07 with IPSAS 27. This research is a qualitative descriptive study. The study was conducted by literature studies, interviewed with related parties, observation, and documentation of the results. The results showed that periodic assessments of biological assets need to be done so that biological transformation could be recorded. Thus the asset values in the financial statements were in accordance with the actual circumstances. However, there were difficulties in applying IPSAS 27, especially in determining market value. The revaluation process at the end of period need cost to be done. It is necessary to conduct a study in advance regarding the readiness of human resources as well as the significance of the costs and benefits of implementing the regulation adopted from IPSAS 27. Local governments need more detailed technical guidelines if the PSAP will adopt IPSAS 27.